Missions or Mission? The IRM after 75 Years - Walls, Andrew F. (International review of mission, 2011)
In 1987, the 75th anniversary issue of IRM reviewed a large number of articles that had been published in the journal over the years. The overall development was a shift from “missions,” as the work of missionaries from the West to the rest of the world, to a focus on “mission,” as that to which all Christians throughout the world are called. The author here raises up emphases from other articles that also could have been included in the 1987 review, because of their implications for future developments. He also points to important trends that have become far more evident since then, such as the growth of churches in the global South and diaspora Christians from these countries who now reside in the North. These may frame the ecumenical challenge for this century.